2018
DOI: 10.1016/j.neuroimage.2018.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Are you thinking what I'm thinking? Synchronization of resting fMRI time-series across subjects

Abstract: We describe BrainSync, an orthogonal transform that allows direct comparison of resting fMRI (rfMRI) time-series across subjects. For this purpose, we exploit the geometry of the rfMRI signal space to propose a novel orthogonal transformation that synchronizes rfMRI time-series across sessions and subjects. When synchronized, rfMRI signals become approximately equal at homologous locations across subjects. The method is based on the observation that rfMRI data exhibit similar connectivity patterns across subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 49 publications
0
48
0
Order By: Relevance
“…In two independent task-fMRI datasets, we showed that 2sDM sufficiently separates between different conditions in task and subjects, suggesting our framework can extract meaningful brain states from fMRI data. While this framework is designed for time-synchronized task fMRI data, recent methods have been developed to create time-synchronized resting-state fMRI data (Joshi, Chong, Li, Choi, & Leahy, 2018). Thus, for future work, we will adapt our framework for resting-state fMRI to investigate brain states when a subject is not explicitly performing a task.…”
Section: Resultsmentioning
confidence: 99%
“…In two independent task-fMRI datasets, we showed that 2sDM sufficiently separates between different conditions in task and subjects, suggesting our framework can extract meaningful brain states from fMRI data. While this framework is designed for time-synchronized task fMRI data, recent methods have been developed to create time-synchronized resting-state fMRI data (Joshi, Chong, Li, Choi, & Leahy, 2018). Thus, for future work, we will adapt our framework for resting-state fMRI to investigate brain states when a subject is not explicitly performing a task.…”
Section: Resultsmentioning
confidence: 99%
“…During the localizer session for this experiment, participants were shown 24 unique grayscale images from each of six stimulus categories: human faces, human bodies without heads, small objects, houses and outdoor scenes comprising of nature and street scenes, and phase scrambled images . During the movie session for this experiment, participants were shown two-hour audio-visual stimuli (the movie Forrest Gump) (Joshi et al, 2018).…”
Section: Datamentioning
confidence: 99%
“…Recently, there have been several interesting approaches [4, 5, 10, 9] that have proposed the synchronization or alignment of fMRI signals primarily for resting state data. Although the end goal in all these methodologies is aligning fMRI time courses to each other, in our work we adopt a different approach.…”
Section: Introductionmentioning
confidence: 99%
“…This issue is similar to the one faced in image/shape registration, where the choice of the template or atlas is critical. Further, the process of alignment itself can be achieved either using a least squares criterion [4, 5] or using the dynamic time warping (DTW) approach [10]. The process of least squares alignment is usually non-elastic and thus doesn’t account for temporal reparameterizations.…”
Section: Introductionmentioning
confidence: 99%